Catholics, Muslims, and Global Politics in Southeast Asia - Sumanto Al Qurtuby (Al-Jami'ah: Journal of Islamic Studies, 2012)
This article discusses the role of catholics, muslims, and civic associations in the global politics of the Philippines and Indonesia. The two countries have shared in common with regard to the geographical feature (both are archipelagic countries), the diversity of societies and cultures, and the history of colonialism, dictatorship, ethno-religious violence, and political movement, to name but a few. In addition to their similarities, both countries also have significant differences in particular pertaining to religious dominance (the Philippines dominated by Catholicism, while Indonesia by Islam) and the structure of their societies: while the Philippines is a class-stratified society, Indonesia has long been ideologized by colonial and post-colonial religious and political powers. Apart from their parallels and distinctions, religion --both Catholicism and Islam-- has marvellous role, negatively or positively, in global politics and public cultures, indicating its vigor and survival in global political domains. This comparative paper, more specifically, examines the historical dynamics of the interplay between religion, civil society, and political activism by using the Philippines and Indonesia as a case study and point of analysis.[Artikel ini mendiskusikan peran Katolik, Muslim dan asosiasi warga dalam politik global di dua negara; Indonesia dan Filipina. Kedua negara tersebut memiliki kesamaan, baik dalam hal ciri geografis sebagai negara kepulauan, keragaman masyarakat dan budayanya, sejarah kolonialisme, pemerintahan diktator, kekerasan etnik-agama, serta gerakan keagamaan. Terlepas dari kesamaan tersebut, keduanya memiliki perbedaan, utamanya menyangkut agama dominan (di Filipina didominasi oleh Katolik, sementara di Indonesia oleh Islam) dan struktur masyarakatnya (Filipina ditandai dengan stratifikasi masyarakat berdasarkan klas sosial, sementara di Indonesia ditandai dengan ideologi agama kolonial, paska-kolonial, politik). Terlepas dari kesamaan dan perbedaan antara keduanya, agama -baik Katolik maupun Islam- memainkan peran penting, baik negatif maupun positif, dalam politik global dan budaya publik. Ini menandai kuatnya peran agama di kedua negara itu. Artikel ini menggunakan analisis perbandingan, utamanya terhadap dinamika sejarah hubungan antara agama, masyarakat sipil, dan aktifisme politik.]